THE INFLUENCE OF OCCUPATIONAL SAFETY AND HEALTH ON EMPLOYEE JOB SATISFACTION AT THE MAIN PORT AUTHORITY OFFICE OF MAKASSAR - Muhammad, Andi Fadel; Anwar, Anwar; Haeruddin, M. Ikhwan Maulana (Jurnal Manajemen, 2025)
Abstract: This study aims to determine whether Occupational Safety and Health has an effect on employee job satisfaction at the Makassar Main Port Authority Office. The approach used is quantitative with a data collection method using a survey. The population in this study was 121 employees with a sample determination of 25% of the population so that 30 employees were obtained. The data analysis technique in this study was multiple regression, which included data quality testing, classical assumption testing, and regression testing. The results showed that occupational safety had a positive and significant effect partially on job satisfaction, occupational health also showed a positive and significant effect on job satisfaction. Simultaneously, occupational safety and health had a positive and significant effect on employee job satisfaction at the Makassar Main Port Authority Office.Keywords: Job Satisfaction, Occupational Safety, Occupational Health